Stereological analysis of capillaries in thick slice of skeletal muscle - Čebašek, Vita (Anali PAZU, 2022)
Stereological analysis of the thick cross sections of fast extensor digitorum longus (EDL) and slow soleus (SOL) muscles was performed and the capillary length to muscle fibre surface area ratio (Lcap/Sfib) evaluated. The Lcap/Sfib ratio of thin oxidative EDL muscle fibres was higher than that of thick glycolytic EDL muscle fibres (35,03 mm-1 ± 1,87 mm-1 : 22,28 mm-1 ± 4,04 mm-1) (p<0,05) and higher than that of oxidative SOL muscle fibres (31,37 mm-1 ± 3,43 mm-1) (p<0,05). Although the thickness of slow oxidative SOL muscle fibres and of fast glycolytic EDL muscle fibres were equal, the ratio Lcap/Sfib of oxidative SOL fibres was higher. The results indicate that the length of capillaries of skeletal muscle fibres correlates well with oxidative capacity of muscle fibres. The Lcap/Sfib ratio offers an insight into muscle fibre metabolism. We believe it can serve as an useful tool for study of skeletal muscle plasticity.